2005
DOI: 10.1029/2004gl021760
|View full text |Cite
|
Sign up to set email alerts
|

Wind driven upwelling along the African coast of the Strait of Gibraltar

Abstract: [1] Regular remote sensing data from various sensors are used here for the study of the wind driven upwelling phenomenon along the African coast of the Strait of Gibraltar. It is shown for an extended summer period (May 15 till September 15, 2003) that sea surface temperature (SST) data in the strait are correlated with NCEP winds, each westward wind increase being followed by a clear surface temperature decrease. Local surface temperature of about 22°C at that time drops down to 15°C, value corresponding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 9 publications
(11 reference statements)
2
23
0
Order By: Relevance
“…The idea of wind-induced coastal upwelling (in the cross-strait direction) versus tidally induced upwelling (in the along-strait direction) has also been reported. In a recent observational study, Stanichny et al (2005) based on high spatiotemporal resolution satellite data showed that wind-driven upwelling phenomena are frequent along the African coast of the Strait of Gibraltar presenting a fast growing 3-D dynamical structure that strongly affects vertical and horizontal water motions and redistribution of biochemical components in the area.…”
Section: Gibraltar Straitmentioning
confidence: 99%
“…The idea of wind-induced coastal upwelling (in the cross-strait direction) versus tidally induced upwelling (in the along-strait direction) has also been reported. In a recent observational study, Stanichny et al (2005) based on high spatiotemporal resolution satellite data showed that wind-driven upwelling phenomena are frequent along the African coast of the Strait of Gibraltar presenting a fast growing 3-D dynamical structure that strongly affects vertical and horizontal water motions and redistribution of biochemical components in the area.…”
Section: Gibraltar Straitmentioning
confidence: 99%
“…U-wind and chl-a in Zone 2 showed a quite synchronised co-variation (Figure 9b,d). The influence of easterlies in our ROI was greater than the influence of westerlies [11,64]. East winds enhance the upwelling of nutrient-rich waters, being more noticeable in Zone 2 together with tidal-bathymetry interaction.…”
Section: Discussionmentioning
confidence: 62%
“…Indeed, the Atlantic jet (AJ) feeds the WAG by means of a meandering structure of ~ 100-150 km of diameter and, occasionally, defines the Eastern Anticyclonic Gyre (EAG) as well ( Figure 1). This dynamic and complex system is regulated by the interaction of local and regional processes [30,32].…”
Section: Study Areamentioning
confidence: 99%
“…The main goal of these efforts was the understanding of the inter-annual variability of biomass in fish species, related to environmental condition. Many studies were realized on the Northern Alboran Sea [15,[30][31][32][33], but very few of them have been carried out on the southern part. We here recognize and analyze fluctuations of sardine's abundance at one of the most important fishing establish the proportional relationship between CPUE and abundance: CPUE = C t / E t = q N t [2] In practice, q is usually considered as a constant.…”
Section: Introductionmentioning
confidence: 99%